Pengaruh Kepercayaan dan Kepuasan Pelanggan terhadap Niat Pembelian Berulang (Patronage Intention) dalam Konteks Ritel Omnichannel - M.Imam Buchory; Nurhasanah Nurhasanah; Eva Ameilia; Tengku Mohd. Khairal Abdullah (Syntax Corporation, 2023)
Rapid advances in technology, coupled with the COVID-19 pandemic, have increased people's online shopping behavior. One of the retail sales schemes that is starting to develop is omnichannel retail where retailers provide a seamless shopping process for their customers. Several grocery retailers currently seem to be trying to implement an omnichannel scheme. Therefore, this study aims to determine whether or not there is an influence on the variables of trust and customer satisfaction towards patronage intention in modern grocery retail stores that have provided omnichannel services. The research method used is quantitative analysis by conducting a survey. The results show that trust has a positive effect on patronage intention, satisfaction has a positive effect on patronage intention and satisfaction mediates the relationship between trust and patronage intention.